Effect of different fertilization strategies on the yield, quality of Euryales Semen and soil microbial community - Li, Dishuai; Qu, Cheng; Cheng, Xuemei; Chen, Yexing; Yan, Hui; Wu, Qinan (Frontiers in Microbiology, 2023)
Introduction Euryales Semen, a medicinal herb widely utilized in Asia, faces a critical constraint in its production, primarily attributed to fertilizer utilization. Understanding the impact of different fertilization schemes on Euryales Semen (ES) planting and exploring the supporting mechanism are crucial for achieving high yield and sustainable development of the ES planting industry. Methods In this study, a field plot experiment was conducted to evaluate the effects of four different fertilization treatments on the yield and quality of ES using morphological characteristics and metabolomic changes. These treatments included a control group and three groups with different organic fertilizer to chemical fertilizer ratios (3:7, 5:5, and 7:3). The results of this study revealed the mechanisms underlying the effect of the different treatments on the yield and quality of Euryales Semen. These insights were achieved through analyses of soil physicochemical properties, soil enzyme activity, and soil microbial structure. Results We found that the quality and yield of ES were the best at a ratio of organic fertilizer to chemical fertilizer of 7:3. The optimality of this treatment was reflected in the yield, soil available nitrogen, soil available phosphorus, and soil enzyme activity of ES. This ratio also increased soil microbial diversity, resulting in an increase and decrease in Proteobacteria and Firmicutes abundances, respectively. In addition, linear discriminant analysis showed that Chloroflexi, Gammaproteobacteria, and Hypocreales-incertae-sedis were significantly enriched in the ratio of organic fertilizer to chemical fertilizer of 7:3. Variance partitioning analysis showed that the soil properties, enzyme activities, and their interactions cumulatively can explain 90.80% of the differences in Euryales Semen yield and metabolome. In general, blending organic and chemical fertilizers at a 7:3 ratio can enhance soil fertility, boost Euryales Semen yield and quality, and bring forth conditions that are agriculturally beneficial to microbial (bacteria and fungi) dynamics. Discussion This study initially revealed the scientific connotation of the effects of different fertilization patterns on the planting of Euryales Semen and laid a theoretical foundation for the study of green planting patterns of Euryales Semen with high quality and yield.